Dilemmas of care (re) allocation: care and consumption in pandemic times - Heath, Teresa (Journal of business ethics, 2025)
Studies into the ethical aspects of consumption tend to focus on a limited class of actions that are explicitly understood as "ethical consumption". The SARS-CoV-2 pandemic provided a context in which other ethical issues and questions of whom we should care for first, and how, suddenly and dramatically gained salience. This article draws on the care literature to explore the reconfiguration of consumption decisions and dilemmas during this period. Building on twenty-eight in-depth interviews, it considers the temporal and spatial dimensions of care and consumption and examines various ethical and ideological considerations that arose, particularly regarding the allocation of care in the face of competing demands. Subsequently, the article problematises mainstream accounts of ethical consumption, arguing for considering a plurality of ethics present within decisions about consumption. It concludes with a call to incorporate a more capacious understanding of care in broader discussions of ethics in consumption.